Developing activities and collaborative networks for sustainable cultural tourism in the local community based on Buddhist cultural heritage in Mueang Chonburi District, Chonburi Province - Thammakamo, Phramaha Suchat (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
The objective of this research article is to study the development of activities and collaborative networks for community-based tourism grounded in sustainable Buddhist cultural traditions in Mueang Chonburi District, Chonburi Province. This study employed a mixed-methods approach, integrating both quantitative and qualitative research methodologies. Data were collected from 400 residents of Mueang Chonburi District and 25 key informants. Research instruments included a questionnaire—with a content validity index of 0.837 and a reliability coefficient of 0.811—as well as an interview form. Data were analyzed using mean, standard deviation, and content analysis. The findings revealed that 1. The study of the potential and tourism routes is at a high level (= 4.09). It is recommended to focus on managing human resources in the community, improving roads and transportation routes to key tourist attractions, and promoting ecotourism that emphasizes environmental conservation. 2. The development of tourism activities is at a high level (= 4.24). It is recommended to promote storytelling through community members, support organizing activities where local people convey knowledge about local rituals, and create connections with Buddhism and local culture that are significant to the community. 3. The development of cooperation and tourism networks is at a moderate level (= 3.48). It is recommended to establish an information center or an online platform, create a central database related to Buddhist community tourism, and conduct surveys to assess the community's needs for necessary resources. 4. The enhancement of tourism is at a high level (= 3.67). It is recommended to create access routes to temples or significant religious sites, ensure good quality roads, provide clear signage, showcase cultural and historical uniqueness, offer convenient public transportation for tourists, and ensure adequate facilities for visitors.